Tumor lysis syndrome associated with chemotherapy in primary retroperitoneal soft tissue sarcoma by ex vivo ATP-based tumor chemo-sensitivity assay (ATP-TCA) - Qian, Ke-Qing (Dove Medical Press, 2009)
Tumor lysis syndrome (TLS), a result of rapid cell lysis following tumor therapy, is a well recognized complication during the treatment of rapidly growing tumors. TLS rarely occurs in solid tumors. We present a case report of TLS in a patient with primary retroperitoneal soft tissue sarcoma. TLS occurred in the patient after four days’ combinational chemotherapy with cisplatin, adriamycin, and dacarbazine. These drugs were selected on the basis of an ex vivo ATP-based tumor sensitivity assay. TLS was properly controlled in the patient with concomitant remission of the sarcoma. Therefore, precautions should be taken to avoid this potentially fatal complication during treatment of solid tumors, especially with tumors highly sensitive to drugs.